2014
DOI: 10.1007/s00438-014-0948-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic evolution of NBS–LRR genes in bread wheat and its progenitors

Abstract: Extensive studies have focused on the largest class of disease resistance genes (nucleotide binding site-leucine-rich repeat, NBS-LRR) in various plants. However, no research on the dynamic evolution of these genes in domesticated species and their progenitors has been reported. Recently published genome sequences of bread wheat and its two ancestors provide a good opportunity for comparing NBS-encoding genes between ancestors and their progeny. Over 2000 NBS-encoding genes have been identified in bread wheat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 62 publications
2
45
1
Order By: Relevance
“…Focus should be diverted toward identification of more Pst resistance genes from wild relatives. More than 2,500 members of the NBS-LRR gene family have been reported in wheat, 570 in Triticum urata , 842 in Aegilops tauschii , 316 in Brachypodium distachyon , and 420 in Hordeum vulgare ( 79 ), and majority of these have potential for disease resistance ( 80 ). Use of bioinformatics tools will help to understand the functions of the NBS-LRR gene family for hunting putative Pst resistance genes.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Focus should be diverted toward identification of more Pst resistance genes from wild relatives. More than 2,500 members of the NBS-LRR gene family have been reported in wheat, 570 in Triticum urata , 842 in Aegilops tauschii , 316 in Brachypodium distachyon , and 420 in Hordeum vulgare ( 79 ), and majority of these have potential for disease resistance ( 80 ). Use of bioinformatics tools will help to understand the functions of the NBS-LRR gene family for hunting putative Pst resistance genes.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…We used the leaf rust isolate #526-24 and stripe rust isolate #5006 from the stocks of the Institute for Cereal Crops Improvement. The virulence / avirulence (V / Av) formula of these isolates is Lr1, 3,24,26,10,18,21,23,15 / Lr2a,2c,9,16,3 ka,11,17,30 and Yr6,7,8,9,11,12,17,19,sk,18, A / Yr1,5,10,15,24,26,sp, for isolates #526-24 and #5006, respectively. Both of these isolates were used to select resistant progenies at the seedling stage and to evaluate adult plant resistance.…”
Section: Pathogensmentioning
confidence: 99%
“…To date, more than 70 resistance genes against leaf rust and stripe rust originating in wheat or in its wild relatives have been identified and mapped [9]. Most of these genes confer seedling resistance although adult plant resistance (APR) genes were also identified [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the conserved domain in the N terminal, the cloned R genes were classified into two types, one type contains the conserved domain resembling the Drosophila Toll and mammalian IL-1 receptors (TIR) and named as TIR subclass, and the other named as non-TIR class (Meyers et al 1999). In the non-TIR class, most NLR genes contain the coiled-coil (CC) domain, and a few NLR genes contain the leucine zipper motif or RPW8 domain (Gu et al, 2015). The genomic data of a number of species have been sequenced, and it was found that dicot species contained both the TIR class and non-TIR class, while the monocot species contained only the non-TIR class.…”
Section: Introductionmentioning
confidence: 99%